2022
DOI: 10.3390/vaccines10071055
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Evaluating Attitudes toward Childhood Immunization among Healthcare Workers in Japan

Abstract: Providing appropriate immunization information during the perinatal period is important for improving immunization rates among infants and children; however, the distribution of immunization information by healthcare workers (HCWs) is not standardized in Japan. We investigated HCWs’ attitudes toward childhood immunization and factors related to vaccine hesitancy. We conducted a cross-sectional descriptive survey of HCWs involved in childhood immunization in Niigata City, Japan, from November 2017 to January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A cross-sectional study of healthcare workers involved in childhood immunization in Niigata City, Japan reported that nurses tend to have a more negative attitude towards vaccination and less awareness of promoting immunization compared to pediatricians. 29 It was thought that organizing in-service pieces of training for nurses on the subject and including vaccination as a separate course in nursing curricula and that of other health professionals would be a useful practice to eliminate nurses' prejudices on the subject and to ensure social confidence in vaccines. 19 In the present study, nurses listed their roles in preventing anti-vaccination attitudes as providing education to parents, counseling, being a role model, increasing knowledge about vaccines, following up-to-date information with courses/congresses/symposiums, conducting evidence-based studies and following current studies/ scientific publications on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of healthcare workers involved in childhood immunization in Niigata City, Japan reported that nurses tend to have a more negative attitude towards vaccination and less awareness of promoting immunization compared to pediatricians. 29 It was thought that organizing in-service pieces of training for nurses on the subject and including vaccination as a separate course in nursing curricula and that of other health professionals would be a useful practice to eliminate nurses' prejudices on the subject and to ensure social confidence in vaccines. 19 In the present study, nurses listed their roles in preventing anti-vaccination attitudes as providing education to parents, counseling, being a role model, increasing knowledge about vaccines, following up-to-date information with courses/congresses/symposiums, conducting evidence-based studies and following current studies/ scientific publications on this subject.…”
Section: Discussionmentioning
confidence: 99%